Kegagalan Analisis Bite mark dalam Identifikasi Forensik - Vanessa Vanessa (Jurnal Kedokteran Gigi Terpadu, 2021)
Forensic odontology is a field of science that applies dental science to solve criminal and civil cases. Bite marks are often used in cases of sexual harassment to murder. However, in reality, several experts, including forensic odontologists, are considered to not mastered the bite mark analysis method properly for suspect identification, which often leads to errors and misinterpretations. This is a very serious matter because it will affect the life of a person. The use of the bite mark method itself in the field of forensic odontology is still a controversial issue because it often leads to misuse and misunderstanding. This review describes the disadvantages of bite mark identification.